Cardioprotective Potential of Ethanol Extract of Sonchus Arvensis L. Leaves on Isoproterenol-Induced Myocardial Infarction in Rat - Neng Fisheri Kurniati; Elin Yulinah Sukandar; Rian Pardilah; Nova Suliska; Dhyan Kusuma Ayuningtyas (Fakultas Farmasi Universitas Pancasila, 2018)
Sonchus arvensis L. leaves have been used traditionally to treat various disease conditions. This study is designed to evaluate cardioprotective potential of ethanol extract of S. arvensis leaves on isoproterenol-induced myocardial infarction in Wistar rat. Male Wistar albino rats were divided into three main groups: negative control (saline only), positive control (isoproterenol only), and S. arvensis extract treated groups. S. arvensis extract was administered in three doses; 50, 100, and 200 mg/kg b.w. p.o for 14 days. On day 13 and 14, isoproterenol (85 mg/kg bw) was given intraperitoneally to positive control and extract treated groups. The parameters studied were cardiac biomarker enzymes which were Creatine Kinase (CK), Creatine Kinase-MB (CK-MB), Aspartate Transaminase (AST), Alanine Transaminase (ALT) and Lactate Dehydrogenase (LDH). The results showed that S. arvensis at dose of 50 mg/kg b.w. could significantly (P<0.05) reduce the level of CK, CK-MB, AST, ALT, and LDH in myocardial infarcted rats compared to positive control. The increase of the dose of S. arvensis extract was not followed by an increase of its cardioprotective activity. In conclusion, Sonchus arvensis L. leaves extract at dose of 50 mg/kg b.w. has potential to be developed as cardioprotective drug.